A review of the Geocoridae of Mexico (Hemiptera: Heteroptera: Lygaeoidea), with descriptions of four new species, new distributional records, and a key to the known subfamilies, tribes, genera and species - Brailovsky, Harry (Zootaxa, 2016)
The family Geocoridae (Hemiptera: Heteroptera: Lygaeoidea) from Mexico is revised. Two subfamilies, one tribe, four genera, and fifteen species are treated in detail and descriptions or redescriptions are provided for all. Four new species of Geocoris are described: G. cervantesi (from Baja California), G. coahuilensis (from Coahuila), G. nuevoleonensis (from Nuevo Leon), and G. signoretae (from Aguascalientes, Hidalgo, and Puebla). The subspecies Geocoris thoracicus wickhami (Montandon) is considered a junior synonym of the nominal species G. thoracicus (Fieber). Key to subfamilies, tribes, genera and species recorded from Mexico are included. New distributional records for all of the previously known species are added. Isthmocoris slevini (Van Duzee) and I. tristis (Stål) are recorded for the first time from Mexico. Notes on the biology of most of the species are included. Color dorsal habitus photos, as well as drawings of the paramere, are included to aid in the identification of the species.